IMPACT OF FINANCING DECISIONS ON PROFITABILITY DIMEDIENT POLICY - Supami Wahyu Setiyowati; Mochamad Fariz Irianto (Universitas Tidar, 2021)
Funding decisions are management decisions in investment financing. Thepurposes of the studies were to determine the impact of funding decisions ondividends policy mediated by profitability. The population of this research iscompanied registered in the Jakarta Islamic Center for the period 2017-2019.The sample selection method is based on the specified criteria. The data'sanalysis technique used parth analysis. The results of the research shows thatfunding decisions have an impact on dividend policy. Profitability affectsdividend policy. Der's proxied funding decision has no effect on profitability.Funding decisions proxied by DER have an effect on profitability. Fundingdecisions affect dividend policy mediated by profitability.